2015
DOI: 10.14393/bj-v31n5a2015-27339
|View full text |Cite
|
Sign up to set email alerts
|

poral dynamic of foraging of epigeic ants in an urban forest fragment

Abstract: ABSTRACT:The present study aimed to investigate the foraging dynamic of an ant community in an urban semideciduous mesophitic forest. A total of 4,297 individuals, distributed in 23 species, seven genera and four subfamilies were sampled in January, April, July and October of 2010. Four ant species guilds were found: leaf cutters, soil-dominant omnivores, soil and vegetation opportunists and large-sized epigaeic predators. There were no significant differences in total of species richness and abundance of indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Rainfall is an important factor in dry ecosystems that triggers animal activity (Wolda, 1978). Some groups of insects are strictly controlled in their seasonality and their abundance by rainfall patterns, being more active and abundant in periods of increased rainfall (Lange et al., 2015; Munique & Calixto, 2018; Wolda, 1978). For instance, Lange, Calixto, Rosa, Sales, and Del‐Claro (2019) showed that abundance of one of the most common foliage‐dwelling ant, Camponotus crassus , in a cerrado sensu stricto vegetation was greater during the months with greater rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…Rainfall is an important factor in dry ecosystems that triggers animal activity (Wolda, 1978). Some groups of insects are strictly controlled in their seasonality and their abundance by rainfall patterns, being more active and abundant in periods of increased rainfall (Lange et al., 2015; Munique & Calixto, 2018; Wolda, 1978). For instance, Lange, Calixto, Rosa, Sales, and Del‐Claro (2019) showed that abundance of one of the most common foliage‐dwelling ant, Camponotus crassus , in a cerrado sensu stricto vegetation was greater during the months with greater rainfall.…”
Section: Discussionmentioning
confidence: 99%